2020
DOI: 10.1016/j.marmicro.2019.101753
|View full text |Cite
|
Sign up to set email alerts
|

From bi-polar to regional distribution of modern dinoflagellate cysts, an overview of their biogeography

Abstract: This paper examines the distribution of 91 modern dinoflagellate cyst taxa from 3636 locations across the world's oceans. Patterns of distributions among the taxa included bipolarity, cosmopolitan, northern versus southern hemispheres, and geographically restricted. Of the 91 taxa, three dominate these assemblages at the global scale, Brigantedinium species, Operculodinium centrocarpum sensu Wall and Dale 1966 and some species of Spiniferites. Whereas Brigantedinium is a true cosmopolitan taxon, with high abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 95 publications
0
57
0
Order By: Relevance
“…are common (Prebble et al, 2013). Selenopemphix antarctica is a species that shows affinity to sea-ice conditions (Zonneveld et al, 2013;Marret et al, 2019).…”
Section: Dinocyst Paleoecological Affinitymentioning
confidence: 99%
See 1 more Smart Citation
“…are common (Prebble et al, 2013). Selenopemphix antarctica is a species that shows affinity to sea-ice conditions (Zonneveld et al, 2013;Marret et al, 2019).…”
Section: Dinocyst Paleoecological Affinitymentioning
confidence: 99%
“…Selenopemphix antarctica, a major component of the modern Antarctic-coastal assemblages(Zonneveld et al, 2013), is never abundant, and present only in few samples (between 390.44-333 mbsf, and at 302 mbsf). I. pallidium, a dinocyst abundant in polar areas of the 310 modern ocean(Zonneveld et al, 2013;Marret et al, 2019) has a scattered low presence throughout the record.…”
mentioning
confidence: 99%
“…The data with back-tracked origin locations can be accessed on planktondrift.science.uu.nl. The datasets with measured dinocysts and planktic foraminifera data are from Marret et al (2019) and Siccha and Kucera (2017) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…High-latitude TEX 86 -SST reconstructions are believed to be skewed towards summer temperatures (Schouten et al, 2013;Ho et al, 2014), but studies around Antarctica have found that archaea appear most abundantly in winter and early spring, with maximum abundances in the subsurface at around 100 m (e.g. Church et al, 2003;Kalanetra et al, 2009;Massana et al, 1998). However, there is a general agreement that TEX 86 captures the relative SST trend (Richey and Tierney, 2016) remarkably well despite these uncertainties, and this will be our main focus when interpreting the results.…”
Section: Tex 86 Overprints and Biasmentioning
confidence: 93%